Tuberculosis in pregnancy: a growing concern - Aftab Khan, Mustafa; Syed Qamar Uddin,; Omer Bin Ahmed, (Journal of the Pakistan Medical Association, 2025)
Tuberculosis (TB) remains one of the most prevalent diseases globally, with an estimated 10.6 million new cases reported in 2022.1 The causative agent is the bacterium Mycobacterium tuberculosis, and its classic symptoms include cough, fever, dyspnoea, chills, stabbing chest pain, and weight loss.2 Although TB is generally considered a curable disease, it can be fatal if left untreated, particularly if contracted during pregnancy. Tuberculosis can affect all stages of female reproduction.3 Therefore, screening and diagnosis are crucial in reducing morbidity and mortality. While pregnancy does not affect disease progression or susceptibility, the outcomes of pregnancy can be severely impacted by TB.4 A meta-analysis conducted by S Sobhy in 2017 demonstrated that active TB in pregnant women significantly increases the risk of maternal morbidity, antenatal admission, miscarriage, anaemia, perinatal death, birth asphyxia, and caesarean delivery.5 Another US-based study led by Erika M. Dennis et al. investigated the effects of active TB on pregnant and non-pregnant women. The study, which comprised 4058 cases, found that active TB in pregnancy resulted in an 80% higher risk of pregnancy complications in pregnant women compared to non-pregnant women. Moreover, the rate of in-hospital deaths among TB-infected pregnant individuals was 37 times higher than that of non-infected pregnant women. These complications included severe eclampsia, severe pre-eclampsia, and postpartum haemorrhage.6 These studies highlight a pressing concern and emphasize the need for measures to mitigate the effects of TB on pregnancy. As TB predominantly affects disadvantaged populations, it is prevalent in underdeveloped and developing countries, such as Pakistan. Consequently, physicians must be aware of how TB can impact diagnosis, prognosis, treatment, and pregnancy outcomes. Furthermore, physicians should educate the general population about TB during pregnancy and prioritize their efforts towards pregnant women who are highly susceptible, such as those residing in impoverished areas or with infected individuals. A more effective approach would involve collaboration between obstetricians, gynaecologists, healthcare providers, and infectious disease specialists. Pregnant women should undergo TB screening if they exhibit symptoms or live in close proximity to TB-infected individuals. These measures will contribute to eradicating the spread of TB and its adverse effects, as well as preventing the transmission of multidrug-resistant TB.